Kinetic and Thermodynamic Studies of Antioxidant and Antimicrobial Activities of Essential Oil of Lavendula steochs - Erum Zahir; Tahira Saleem; Humaira Siddiqui; Shaista Naz; Syed Muhammad Shahid (Journal of Basic & Applied Sciences, 2015)
Antioxidant, antimicrobial activities of essential oil from plant Lavendula steochs were studies bykinetics and thermodynamic approach. Hydro-distillation was used for the extraction of oil from the flowers of Lavendula steochs. - Antioxidant activity was performed using DPPH method, in which the IC50 showed that essential oil has good antioxidant activity. Antimicrobial activity has been analyzed against Methicillin-resistant Staphlococcus aureus (MRSA) and Vancomycin-resistant Staphlococcus aureus (VRSA) which shows that Lavendula steochs is found to be effective against MRSA andVRSA. Chemical composition of essential oils were measured by GC-MS and FT-IR techniques and the kinetic & thermodynamic parameters were used for the characterization of essential oils.